Liquid–liquid phase separation of the green mussel adhesive protein Pvfp-5 is regulated by the post-translated Dopa amino acid - Deepankumar, Kanagavel (2022)
The underwater adhesive prowess of aquatic mussels has been largely attributed to the presence of the post-translationally modified amino acid 3,4-dihydroxylphenylalanine (Dopa) in mussel foot proteins (MFPs) that make up their adhesive threads. In parallel, it has been suggested that during thread fabrication, MFPs form intermediate fluidic phases such as liquid crystals or coacervates during a Liquid-Liquid Phase Separation (LLPS) process. Here, we show that Dopa plays another central role during mussel fiber formation, by enabling LLPS of Pvfp-5, a main MFP of the Asian green mussel Perna viridis. Using residue-specific substitution of Tyrosine (Tyr) for Dopa during recombinant expression, we show that Dopa-substituted Pvfp-5 exhibits LLPS under seawater-like conditions, whereas the Tyr-only version forms insoluble aggregates. Combining quantum chemistry calculations and solution NMR studies, we find that a transient H-bonding network requiring the two hydroxyl groups of Dopa is critical to enable LLPS in Dopa-mutated Pvfp-5. Overall, our study suggests that Dopa plays an important role in regulating LLPS of MFPs, which may be critical to concentrate the adhesive proteins at the plaque/substrate interface and therefore produce a more robust adhesive. Our findings also provide molecular-level lessons to guide biomanufacturing of protein-based materials such as bioadhesives and load-bearing fibers.